Developing the Performance of Heads of Scientific Departments at King Faisal University in the Light of the Transformational Leadership Approach from the point of view of the faculty members - Al-Shammari, Fahad Dhari (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the degree of the practice of the heads of scientific departments of transformational leadership at King Faisal University from the point of view of the faculty members, and the requirements of developing the performance of the heads of scientific departments, and to provide a proposed vision to develop the administrative performance of heads of scientific departments in Saudi universities in the light of transformational leadership. To achieve the objectives of the study, the descriptive method was used in a manner appropriate to the nature of this study. The sample of the study consisted of (166) faculty members. The study reached several results, including that the degree of practicing the heads of the scientific departments of transformational leadership at King Faisal University from the point of view of the faculty members within the average grade of average medium average (3.61), and there were no statistically significant differences due to gender variables, and the number of years of experience, and academic rank, With the exception of the field of empowerment, where the results showed the presence of statistically significant differences for the benefit of the rank of professor, and the results showed that the most important requirements for the development of the performance of the heads of scientific departments in Saudi universities in the light of the transformative leadership approach from the viewpoint of faculty members, was the formation of a general To evaluate and suggestions of faculty members and staff in the department, and create an attractive environment based on communication between employees and touch their needs and concerns, and facilitate the work procedures to be clear to all without complication, and in the light of the theoretical literature of the study and the relevant scientific studies, and the results of the field study has been proposed to develop The performance of heads of scientific departments in the light of transformational leadership. In the light of the results of the study, several recommendations were made, including the provision of a favorable climate for the practice of stimulation and excitement at King Faisal University, and the university's call for the need to design a performance evaluation system for heads of scientific departments based on sound scientific bases, which has the ability to measure the performance of each department head and its contribution to achieving goals Department and College.
Keywords: performance of department heads; transformational leadership; King Faisal University